2013
DOI: 10.1007/s10347-013-0372-2
|View full text |Cite
|
Sign up to set email alerts
|

Arctic rhodolith beds and their environmental controls (Spitsbergen, Norway)

Abstract: Coralline algae (Corallinales, Rhodophyta) that form rhodoliths are important ecosystem engineers and carbonate producers in many polar coastal habitats. This study deals with rhodolith communities from Floskjeret (78A degrees 18'N), Krossfjorden (79A degrees 08'N), and Mosselbukta (79A degrees 53'N), off Spitsbergen Island, Svalbard Archipelago, Norway. Strong seasonal variations in temperature, salinity, light regime, sea-ice coverage, and turbidity characterize these localities. The coralline algal flora co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 67 publications
3
65
0
Order By: Relevance
“…This specimen was most closely related to L. Teichert et al (2014). Our molecular analysis confirmed that these samples were dominated by L. glaciale, but we also identified a specimen of L. 15 lemoineae Adey from our sub-sampling of this collection.…”
Section: Resultssupporting
confidence: 67%
“…This specimen was most closely related to L. Teichert et al (2014). Our molecular analysis confirmed that these samples were dominated by L. glaciale, but we also identified a specimen of L. 15 lemoineae Adey from our sub-sampling of this collection.…”
Section: Resultssupporting
confidence: 67%
“…Teichert et al (2012Teichert et al ( , 2014 also showed obvious similarities between the populations, with Lithothamnion glaciale as the dominating photoautotrophic organism at water depths around 45 m, appearing as encrustations or rhodoliths. The colonized substrate is mainly made up of glaciogenic debris and dropstones, and grazing organisms like chitons and echinoids are present at all sites, presumably contributing to keep the rhodoliths free from epibionts (Steneck, 1986).…”
Section: Discussionmentioning
confidence: 93%
“…The rhodoliths also act as bioengineers sensu Jones et al (1994) and provide microenvironments for the benthic organisms, which therefore depend on substantial rhodolith growth. Teichert et al (2012Teichert et al ( , 2014; note increased CaCO 3 production rate in combination with deviating water depth at NKB #714. To gain data on the annual rhodolith CaCO 3 production, a method was used that enabled the analysis of large sample sizes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations